Suspicious for Malignancy Diagnoses on Pleural Effusion Cytology - Erika F. Rodriguez (2020)
© American Society for Clinical Pathology, 2020. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com. OBJECTIVES: A definitive diagnosis of malignancy may not be possible in pleural effusions. We report our experience with the diagnosis of suspicious for malignancy (SFM) in pleural effusion. METHODS: A search for pleural effusions diagnosed as SFM (2008-2018) was performed. Patient records and pathology reports were reviewed. Specimens were subdivided into groups depending on volume (<75, 75-400, >400 mL). Diagnoses of malignant pleural effusion (MPE) served as controls. RESULTS: We identified 90 patients, with a mean age of 60.6 years. Diagnoses included suspicious for involvement by carcinoma/adenocarcinoma in 64.4%, leukemia/lymphoma in 15.6%, melanoma in 2.2%, sarcoma in 3.3%, germ cell tumor in 1.1%, and not otherwise specified in 13.3%. Immunostains were performed in 47.8% and considered inconclusive in 24%. Average sample volume was 419 mL. There was a statistically significant difference between the SFM vs MPE groups for volumes greater than 75 mL (P = .001, χ 2 test), with SFM having increased proportion of volumes  greater than 400 mL, compared with the MPE group. There was no statistically significant difference in mean overall survival when the groups were compared (P = .49). CONCLUSIONS: Samples with low cellularity, scant cell blocks, and inconclusive immunostains may contribute to a suspicious category diagnosis in pleural effusions.